The corrosion of reinforcing bars in concrete using pyroclastic fall deposits, i.e. lahar, as aggregates - Torre, Margarita T. (1993)
The corrosion of reinforcing bars in concrete using pyroclastic fall deposit (PFD), i.e. lahar, as aggregate was studied. Electrochemical techniques were primarily used for the evaluation, however, characterization of the materials through identification of elemental composition, estimation of neutralization rates of the mortar and determination of the chloride penetration were also included in the investigation. Results of the investigation showed that in 5% NaCl solution, the current density of embedded steel in PFD mortar is less than one-half of the current density of steel in natural riversand mortar. Furthermore, in a long term exposure to chloride contaminated environment, the risk of steel corrosion is lower in PFD concrete. In the thermodynamic or equilibrium state, steel behaves similarly in the two kinds of mortar.
The water-soluble chloride content of PFD is low compared to the considered threshold value. The estimated ration of carbonization/neutralization based on compressive strength showed that the rate in PFD is 1/1.7 times the rate of neutralization in a riversand mortar. Likewise, the depth of chloride penetration is also lower by 50 - 60%.
Computer print-out.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Corrosion and anti-corrosives.; Cement -- Corrosion; Steel -- Corrosion; Volcanic ash, tuff, etc